Respon Pertumbuhan dan Hasil Tanaman Kacang Panjang (Vigna sinensis. L) Akibat Pemberian Pupuk Bokashi Kotoran Ayam dengan Tinggi Lanjaran yang Berbeda - Aldi Sarianto; Lukman Lukman; Rian Christian Sondakh (Permaculture: Jurnal Ilmu Pertanian & Lingkungan, 2026)
This study aimed to determine the interaction effect between chicken manure bokashi fertilizer and different trellis heights on the growth and yield of yardlong bean. The research was conducted from May to July 2025 at the agricultural field of Madako University, located in Tambun Subdistrict, Baolan District, Tolitoli Regency. A factorial randomized block design (RBD) was used with two factors. The first factor was the application of chicken manure bokashi with three levels: P0 (no fertilizer/control), P1 (100 g/plant), and P2 (166 g/plant). The second factor was trellis height with three levels: K1 (1.5 meters), K2 (2 meters), and K3 (2.5 meters). There were 9 treatment combinations, each repeated 3 times, resulting in 27 experimental plots, each measuring 100 cm × 200 cm. Each plot contained 12 plants, totaling 324 plants, with a spacing of 30 cm × 50 cm. Five sample plants were taken per plot, making a total of 135 sample plants.  The results showed that the growth and yield response of yardlong bean (Vigna sinensis L.) was significantly and highly significantly affected by the interaction between chicken manure bokashi and trellis height. The best treatment was P2K2 (166 g/plant of chicken manure bokashi and 2-meter trellis height), which resulted in the best average values in the following generative parameters: days to flowering (36.47 DAP), number of pods (7.11 pods), pod weight (30.47 g), and pod length (64.11 cm).